Cuticular hydrocarbons as biomarkers of developmental stages in Thanatophilus sinuatus (Fabricius, 1775) (Coleoptera: Staphylinidae): evidence from GC–MS and random forest modeling - Sharif, Swaima; Jakubec, Pavel; Moore, Hannah E.; Cody, Robert B.; Amendt, Jens; Qamar, Ayesha (Springer, 2026)
The analysis of cuticular hydrocarbon (CHC) profiles can provide valuable insights into species identification, immature development and adult ageing, sexual communication, reproductive functions, and other physiological processes of insects. This study investigated the CHC profiles across the life stages of Thanatophilus sinuatus (Fabricius, 1775), a carrion beetle species commonly associated with decomposing tissues, including human remains. We examined the first, second, and third larval instars, the pupa, and the adult male and female using gas chromatography–mass spectrometry. A total of 56 CHCs were identified, including n-alkanes, branched alkanes, and alkenes. Branched alkanes were dominant throughout development, while significant compositional differences were observed among stages. Certain compounds showed consistent proportions across development, suggesting roles in physiological or behavioral processes. Gender-specific differences were also evident, with some CHCs detected exclusively in males or females, potentially linked to sexual communication and reproductive functions. Principal component analysis revealed distinct clustering of developmental stages, and Random Forest classification with out-of-bag validation confirmed high predictive accuracy of CHC profiles for developmental stage identification. These findings highlight the potential of CHC profiling, combined with machine learning approaches, as a valuable tool, particularly useful in situations where specimens of T. sinuatus or other related species are damaged, incomplete, or present only as chemical residues, rather than when intact larvae are available. CHC profiling offers a complementary method for cases where diagnostic characters are missing or obscured.
Keywords: 3109 Zoology; 41 Environmental Sciences; 31 Biological Sciences; Machine Learning and Artificial Intelligence; Women's Health; General Science & Technology; Cuticular hydrocarbons; Staphylinidae; Life stages; n-alkanes; Branched alkanes; Confusion matrix